Assessment of wound healing in relation to nutritional status of the patients in common surgical condition in tertiary care centre - Singh, Rahul; Tripathi, Shashank Shekhar; Tripathi, Ankur; Pandey, Himansha (International Surgery Journal, 2019)
Background: Wound healing depends upon a balance between general factors which include nutritional status of the patient and local factors. Assessment of wound healing in relation to nutritional status of the patients in common surgical conditions. Methods: 46 surgical patients admitted in S.R.N. Hospital, Motilal Nehru Medical College, Allahabad during the period from July 2017 to July 2018, were included. Clinical, anthropometric examination, assessment of wound healing and factors affecting wound healing was done. Results: The mean age of the males patients were 38 years and that of female 33 years. Out of 46 patients included in our study 71.74% were male and 28.26% were females, and among these 15.15% of male and 38.46% female were malnourished. Percentage of wound contraction was 11.38% among the healthy and 2.30% in malnourished group, while the percentage of infection was 14% and 13% among healthy males and female and 20% each for malnourished males and females. Loss of weight was 9.4% and 10.1% among healthy male and female and 6.54% and 7.5% for malnourished male and females. The percentage of wound disruption in our study was 9% among malnourished group. Conclusions: Wound infection and disruption collectively increased the mortality and morbidity significantly in patients of malnourished group. Socio economic status has indirect correlation with wound healing. Malnourishment has a definite effect on wound healing.